Fibrin Clot Structure and Mechanics Associated with Specific Oxidation of Methionine Residues in Fibrinogen - Weigandt, Katie M. (The Biophysical Society, 2012)
Using a combination of structural and mechanical characterization, we examine the effect of fibrinogen oxidation on the formation of fibrin clots. We find that treatment with hypochlorous acid preferentially oxidizes specific methionine residues on the α, β, and γ chains of fibrinogen. Oxidation is associated with the formation of a dense network of thin fibers after activation by thrombin. Additionally, both the linear and nonlinear mechanical properties of oxidized fibrin gels are found to be altered with oxidation. Finally, the structural modifications induced by oxidation are associated with delayed fibrin lysis via plasminogen and tissue plasminogen activator. Based on these results, we speculate that methionine oxidation of specific residues may be related to hindered lateral aggregation of protofibrils in fibrin gels.